Penerapan WebQual 4.0 dan End User Computing Satisfaction Dalam Mengukur Kepuasan Serta Loyalitas Pengguna Website Codashop - Ricky Maulana Sinurat; Dedy Setiawan; Mohamad Ilhami (JSI: Jurnal Sistem Informasi (E-Journal), 2025)
The rapid development of internet and smartphone technology affects the online gaming industry in Indonesia. User satisfaction in the gaming industry is also supported by the development of game voucher top-up platform services, one of which is Codashop. Measuring user satisfaction with the quality of this website requires a method to see the level of user satisfaction with website quality, namely the WebQual 4.0 method and End User Computing Satisfaction (EUCS). The WebQual 4.0 method is a method of measuring the quality of a website from the end-user perspective in order to improve the quality of website performance so that website development can be improved and developed. Meanwhile, End User Computing Satisfaction is a method of measuring user satisfaction so that a comprehensive system evaluation is carried out based on user experience. The variables used include Usability, Information Quality, Service Interaction Quality, and Content. The hypothesis was tested using 5 hypotheses, 3 of which were accepted and 2 were rejected, namely Usability has no positive effect on User Satisfaction, Information Quality Satisfaction affects User Satisfaction, Service Interaction Quality has no positive effect on User Satisfaction, Content affects User Satisfaction, and User Satisfaction affects User Loyalty.